Al-Juffali v. Estrada. (2020) - Unknown
Abstract : International organizations — Immunities and privileges — Jurisdictional immunity — Representative to international organization — Permanent Representative to International Maritime Organization — Headquarters Agreement between United Kingdom and International Maritime Organization — International Maritime Organization (Immunities and Privileges) Order 2002 — Whether court entitled to conduct functional review of appointment of Permanent Representative Jurisdiction — Immunity — Diplomatic immunity — International organizations — Permanent Representative to international organizations — United Nations Convention on the Privileges and Immunities of Specialized Agencies, 1948 — Vienna Convention on Diplomatic Relations, 1961 — Permanent residents only entitled to immunity in exercise of official functions — Definition of permanent residency — The law of England